2020
DOI: 10.1038/s42005-020-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductance across harmonic-matched epitaxial Al-sapphire heterointerfaces

Abstract: A unified fundamental understanding of interfacial thermal transport is missing due to the complicated nature of interfaces. Because of the difficulty to grow high-quality interfaces and lack of materials characterization, the experimentally measured thermal boundary conductance (TBC) in the literature are usually not the same as the ideally modelled interfaces. This work provides a systematic study of TBC across the highest-quality (atomically sharp, harmonic-matched, and ultraclean) epitaxial (111) Al||(0001… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 92 publications
6
39
0
Order By: Relevance
“…A recent work by Cheng et al claimed that no inelastic phonon transport is observed in atomically sharp Al/Al2O3 interface grown by MBE 6 . We would like to point out that at least 5 monolayers of Al2O3 near the interface are distorted, as shown in their TEM image, which is similar to our Al/Si Sample 2 and not as sharp as our Al/Si Sample 1.…”
Section: With Increasing Interface Roughness Inelastic Phonon Transport Rapidly Diminishes Our Results Provide New Insights On Phonon Tramentioning
confidence: 99%
See 4 more Smart Citations
“…A recent work by Cheng et al claimed that no inelastic phonon transport is observed in atomically sharp Al/Al2O3 interface grown by MBE 6 . We would like to point out that at least 5 monolayers of Al2O3 near the interface are distorted, as shown in their TEM image, which is similar to our Al/Si Sample 2 and not as sharp as our Al/Si Sample 1.…”
Section: With Increasing Interface Roughness Inelastic Phonon Transport Rapidly Diminishes Our Results Provide New Insights On Phonon Tramentioning
confidence: 99%
“…The scattering of heat carriers, predominately phonons, leads to interface thermal resistance. Over the past several decades, there were extensive studies on thermal conductance across metal/semiconductor interfaces, both experimentally and theoretically [6][7][8][9][10][11][12] . However, the rare agreement between experiments and calculations as well as the scattered experimental results even for the same interface warrant study for much better understanding of thermal transport across interfaces 6,[13][14][15] .…”
Section: With Increasing Interface Roughness Inelastic Phonon Transport Rapidly Diminishes Our Results Provide New Insights On Phonon Tramentioning
confidence: 99%
See 3 more Smart Citations